Research on the design and application of a monitoring device for bidirectional deformation cracks. Issue 3 (May 2019) - Li, Kai-ren; Han, Shangyu; Li, Yueming
Abstract: The cracks development of geotechnical structures can be generally summarized as transverse deformation and vertical deformation. In order to reduce the difficulty of cracks monitoring and analysis, this paper designs a monitoring device for bidirectional deformation cracks, and analyzes the monitoring principle and scheme of the monitoring device. According to the practical need of bidirectional deformation measurement of geotechnical structures, a set of simple and practical monitoring device is prepared. From the test results, it can be seen that the monitoring device of a monitoring device for bidirectional deformation cracks is convenient to prepare and has high test accuracy, which can meet the monitoring needs of geotechnical structure bidirectional deformation.